Bridging the Gap Between Planned and Enacted Character Education in 21st-Century Physics Learning - Fitriyawany, Fitriyawany; Meutiawati, Ida; Susanti, Susanti; Shalihah, Nadiatun; Nazim, Nur Farah Syahirah (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Character education has become a key priority in Indonesia's educational reform, yet its integration into physics learning remains inconsistent. Existing studies have largely emphasized curriculum frameworks and instructional models, while empirical evidence on how physics teachers implement character education in classroom practice remains limited. This study investigated the challenges of embedding the Strengthening Character Education (PPK) values into 21st-century physics learning and identified strategies to strengthen its implementation in senior high schools in Banda Aceh. A convergent mixed-methods design was employed, combining semi-structured interviews, classroom observations, lesson plan analysis, and surveys involving physics teachers and students from accredited schools. The findings revealed a clear gap between planned and enacted character education. Although character values and 21st-century competencies were consistently incorporated into lesson plans, their classroom implementation remained partial and inconsistent. The main barriers included limited instructional time, strong emphasis on cognitive achievement, insufficient professional development, and the absence of standardized character assessment practices. Teachers generally perceived character integration more positively than was evident from classroom observations, indicating a discrepancy between intended and enacted practice. This study provides empirical evidence explaining how teacher readiness, pedagogical beliefs, institutional support, and curriculum demands collectively shape character integration in physics learning. The findings offer practical guidance for strengthening teacher professional development, assessment practices, and evidence-based policies supporting character-oriented physics education in Indonesia.